The Influence of Liquidity, Solvability, and NPF to the Profitability and the Size of Company as a Moderation Variable - Annisa Putri Nurdin; Tiara Juliana Jaya (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
This research is motivated by the instability of profitability experienced by Islamic Commercial Banks in Indonesia over the past five years. This paper aims to analyze the effect of liquidity, solvency, and Non-Performing Financing (NPF) on profitability with company size as a moderating variable in Islamic Commercial Banks in Indonesia from 2019-2023. The data used in this study are secondary data obtained from the financial statements of banks registered with the Financial Services Authority (OJK). The analysis method used in this study is panel data regression with Moderated Regression Analysis (MRA). The study results indicate that liquidity and solvency have a positive and significant effect on profitability, while NPF has a negative and significant effect on profitability. Firm size can moderate the relationship between liquidity and profitability and the relationship between solvency and profitability, but firm size cannot moderate the relationship between NPF and profitability. The implications of this study indicate the importance of liquidity management, debt control, and management of problematic financing in improving the profitability performance of Islamic banks.